The effectiveness of environment-oriented e-books based on problem-based learning for problem-solving skills - Wintari Ningsih; Baskoro Adi Prayitno; Slamet Santosa (University of Muhammadiyah Malang, 2023)
This study aims to test the effectiveness of using environment-oriented e-books based on Problem-Based Learning (PBL) to empower problem-solving skills. The research design used is a Nonrandomized Control Group, Pretest-Posttest Design. The study used a quasi-experimental method with a 2 x 2 factorial design. The research sample was 70, grade X students of Colomadu State High School. The sample was divided into two groups: the control group using powerpoint media and conventional learning models and the treatment group using PBL-based environment-oriented e-books. The material used in the research is ecosystems in biology subjects. The instrument used to obtain data on problem-solving skills is an essay test. Data analysis using ANCOVA (p = 0.05%) with pretest value as a covariate. The results showed that PBL-based environment-oriented e-books had the most significant increase in problem-solving skills scores compared to the control class.